Combining Ability and Gene Action - Verma, RS; Pratap, Narendra; Dubey, DK; Singh, SS (SAARC Journal of Agriculture, 2014)
The investigation was carried out to get information regarding magnitude of combining ability and nature of gene action for fruit yield and several other yield attributing traits following line × tester mating design involving 12 lines and 3 testers and their 36 hybrids tested in two environments viz., summer and rainy season 2010 at Research Farm of Department of Vegetable Science, N. D. University of Agriculture & Technology, Kumarganj, Faizabad, UP, India. From the estimate of gca effects, among the parental lines NDBT-13, NDBT-15 and NDBT-19 were identified as superior donor for both seasons and NDBT-10 for summer season and among the testers Kalyanpur Sona for summer season and Pusa Do Mausami for rainy season for fruit yield per plant and its yield contributing traits like number of fruits per plant and average fruit weight. Eight crosses displayed desirable significant sca effects in both seasons for fruit yield per plant. Among these eight crosses the best cross combinations based on desirable sca effects for fruit yield per plant were NDBT-19 × Pusa Do Mousami in summer season while NDBT-8 × Pusa Do Mousami, NDBT-15 × NDBT-12 and NDBT-10 × Pusa Do Mousami in rainy season. These crosses have more number of fruits per plant, average fruit weight, fruit diameter and other component traits in both seasons. DOI: http://dx.doi.org/10.3329/sja.v11i2.18407 SAARC J. Agri., 11(2): 117-127 (2013)